LGB bireylerin ailelerine açılma süreçlerinde karşılaştıkları travmatik durumların fenomenolojisi - Güzel, Amine (İstanbul Bilgi Üniversitesi, 2019)
The aim of this study is to provide an in-depth understanding of LGB individuals’ traumatic experiences in disclosing to their families. For this purpose, how LGB individuals experienced the processes of the awareness and acceptance of their own sexual orientation, how homosexuality and bisexuality are perceived in their families, what processes they went through when disclosing to their families, and what traumatic experiences are involved through these processes have tried to be understood. For the purpose of the research, in-depth interviews were conducted with a total of six, two in each, volunteer participants on lesbian, gay and bisexual sexual oriented. These interviews were conducted in accordance with the ‘Interpretative Phenomenological Analysis’ method and analyzed using this method. As a result of these analyzes, 28 second level subordinate themes, 18 first level subordinate themes and 5 superordinate themes determined according to the common characteristics of these themes were reached. These superordinate themes are listed as “Family and LGB Individual”, “LGB Individual’s Awareness and Acceptance Process of Their Own Sexual Orientation”, "Disclosure to Family", "After Disclosure to Family" and "The Conditions Representing Freedom for LGB Individuals”. It was observed that the findings obtained in the study contain many traumatic experiences. These findings were compared with the existing literature and each superordinate theme is associated with the relevant concept of trauma. In addition, contributions to clinical practice and recommendations for future research were discussed.

Bu çalışmanın amacı, LGB bireylerin ailelerine açılma süreçlerinde karşılaştıkları travmatik durumları derinlemesine anlamaktır. Bu amaçla LGB bireylerin; ailelerinde eşcinselliğin ve biseksüelliğin nasıl algılandığı, kendi cinsel yönelimlerine dair farkındalık ve kabul süreçlerini nasıl deneyimlediği, ailelerine açılırken ne gibi süreçlerden geçtikleri ve sıralanan tüm bu süreçlerin LGB bireyler açısından ne gibi travmatik durumları barındırdığı anlaşılmaya çalışılmıştır. Araştırmanın amacı doğrultusunda lezbiyen, gey ve biseksüel cinsel yönelimlerinin her birinden ikişer kişi olmak üzere, toplam altı gönüllü katılımcı ile derinlemesine görüşmeler gerçekleştirilmiştir. Bu görüşmeler ‘Yorumlayıcı Fenomenolojik Analiz’ yöntemine uygun olarak gerçekleştirilmiş ve yine bu yöntem kullanılarak analiz edilmiştir. Bu analizler sonucu 28 adet ikinci düzey alt tema, 18 adet birinci düzey alt tema ve bu temaların ortak özelliklerine göre belirlenen 5 adet üst düzey temaya ulaşılmıştır. Bu üst düzey temalar; “Aile ve LGB Birey”, “LGB Bireylerin Cinsel Yönelimine Dair Farkındalık ve Kabul Süreci”, “Aileye Açılmak”, “Aileye Açılma Sonrası” ve “LGB’ler İçin Özgürlüğü Temsil Eden Koşullar” olarak sıralanır. Araştırmada elde edilen bulguların, birçok travmatik durumu barındırdığı görülmüştür. Bu bulgular mevcut literatürle karşılaştırılmış ve belirlenen her üst düzey tema, ilgili travma kavramı ile ilişkilendirilmiştir. Ayrıca, çalışmada klinik uygulamalara katkılar ve gelecek araştırmalara öneriler ele alınmıştır.